A Legal Perspective on The Transformation of Health Services with Artificial Intelligence - Siregar, Rospita Adelina (Soepra Jurnal Hukum Kesehatan, 2023)
Artificial Intelligence (AI) in medical services is expected to have a significant impact on the world of medicine. The research, which is a literature review, data collection, observation, analysis, is finally presented descriptively as a normative juridical study. The potential for AI to contribute the diagnostic process and even replacing the role of doctors is growing. Currently the use of AI has been utilized in medicine (registration, medical records, images, treatment, telemedicine, outbreak) and health resources.AI as an electronic agent operator is recognized as having a legal position, seen from Law number 19 of 2016 concerning electronic information and transactions (ITE Law) and PP 71/2019 concerning the implementation of electronic systems and transactions, regulating the limits of obligations and responsibilities of Electronic Agent organizers. In a trade context, hospitals are "intermediary traders" here a "last moving" agreement or "instruction agreement" applies. Then providing services automatically refers to article 1 of the ITE Law, if a dispute occurs then legal responsibility is borne by the electronic system operator providing AI services. Settlement refers to Article 38 and Article 39 of the ITE Law through court (Claass action and Civil Lawsuit) or non-litigation settlement.Abstrak: Kecerdasan Buatan (AI) dalam pelayanan medis diharapkan dapat memberikan dampak yang signifikan terhadap dunia kedokteran. Penelitian yang berupa tinjauan pustaka, pengumpulan data, observasi, analisis, akhirnya disajikan secara deskriptif sebagai penelitian yuridis normatif. Potensi AI untuk berkontribusi dalam proses diagnostik dan bahkan menggantikan peran dokter semakin besar. Saat ini pemanfaatan AI telah dimanfaatkan dalam bidang kedokteran (registrasi, rekam medis, pencitraan, pengobatan, telemedicine, wabah) dan sumber daya kesehatan. AI sebagai penyelenggara agen elektronik diakui mempunyai kedudukan hukum, dilihat dari Undang-undang nomor 19 tahun 2016 tentang informasi dan transaksi elektronik (UU ITE) dan PP 71/2019 tentang penyelenggaraan sistem dan transaksi elektronik, mengatur batasan kewajiban dan tanggung jawab penyelenggara Agen Elektronik. Dalam konteks perdagangan, rumah sakit adalah “pedagang perantara” di sini berlaku perjanjian “perjanjian perpindahan terakhir” atau “perjanjian instruksi”. Kemudian pemberian layanan secara otomatis mengacu pada pasal 1 UU ITE, apabila terjadi perselisihan maka tanggung jawab hukum ditanggung oleh penyelenggara sistem elektronik penyedia layanan AI. Penyelesaiannya mengacu pada Pasal 38 dan Pasal 39 UU ITE melalui pengadilan (gugatan kelompok dan Gugatan Perdata) atau penyelesaian non-litigasi.